Humoral, cellular immunity and efficacy of bioreactor propagated and inactivated Fowl adenovirus 8b adjuvanted with Montanide 71VG in broiler chickens. - Ugwu, Chidozie C; Hair-Bejo, Mohd; Nurulfiza, Mat I; Omar, Abdul R; Ideris, Aini (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The study aimed to inactivate the FAdV isolate (UPM11142P5B1) produced in a bioreactor and assess the humoral and cellular immunity, efficacy, and virus shedding in broiler chickens. Materials and Methods: The isolate was grown in a bioreactor, inactivated using binary ethyleneimine, adjuvanted with Montanide 71VG, and injected into day-old broiler chickens either with or without booster groups. The following parameters were measured: T lymphocyte profile in the liver, spleen, and thymus; FAdV antibody titer; clinical symptoms; gross and histological alterations in the liver, spleen, and thymus; virus copy number in the liver and cloacal shedding. Results: Compared to the unchallenged control group, booster (BG), and non-booster (NBG), the challenged control group (CCG) had a larger liver: body weight (BW) ratio, milder clinical signs, gross lesions, and histological alterations. They also had a lower BW. At 7, 21, 35, and 42 days post-inoculation (dpi), the NBG and BG exhibited higher antibody levels than the UCG. At 35 dpi, challenged BG and NBG produced more antibodies than CCG. In BG and NBG, T cells were stimulated in the spleen, thymus, and liver. At 35 and 42 dpi, the challenged BG and NBG showed significantly decreased viral copy numbers in the liver and shedding, respectively, along with increased lymphocyte counts. Conclusion: The inactivated UPM11142P5B1 with Montanide 71VG could be a vaccine against FAdV 8b infections in chickens. J. Adv. Vet. Anim. Res., 11(3): 693–702, September 2024 http://doi.org/10.5455/javar.2024.k819